(3JMaI GdJGdj hOQLI GdeYGdjs - (3EHQGgje Hf CMeO Hf HOQ GdWhdhf GdZeQj GdTGaYjs ((3GdMGL MSf Hf GdMGL eMeO Hf GdMGL YHOGdUeO GdUfHGWj s)
(3ChdgG (B:s
(3hHYO ajbhd EHQGgje Hf CMeO SCdfj HYV GdCYRI Ydj ef GdaVdGA GdeJQOOjf Edi Cf CVa hQjbGJ bdGFd s
(3BNQgG (B:s
(3EPG cGf GdMQa GdCNjQ , ef cd cdeI efgG ecShQ dGZjQ hgPG BNQ eG SFdfG Yfg eNJUQkG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B473 - (3U(B481s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3eLGejY (B123) s
Keywords: (3GdbQGAGJ hGdJLhjOs